Human Rights and the Energy Transition: Challenges, Prospects, and the Importance of a Just Transition - Augustyn-Skuza, Paulina; Skuza, Maciej (Studia Iuridica Toruniensia, 2026)
The energy transition is a dynamic socio-economic process leading to far-reaching changes towards a circular economy, aimed at slowing down anthropogenic climate change and environmental degradation resulting from the industrial history of humanity. Despite its liberal character, with the overarching goal of improving the living conditions of people and future generations in accordance with the principles of sustainable development, the energy transition also entails a number of challenges for the protection of human rights. The growing industry related to low-emission technologies, particularly in the countries of the Global South, is already contributing to gross violations of fundamental human rights, exacerbating existing inequalities. The purpose of this article is to examine the relationship between the energy transition process and the protection of human rights, taking into account the concept of a just energy transition, which focuses on respect for human dignity and on fair and ethical access to resources.